Tata Rias Wajah, Foundation Liqu PERBANDINGAN PROPORSI FOUNDATION LIQUID DAN CREAM TERHADAP HASIL TATA RIAS WAJAH MODEL KATALOG PRODUK - Alfin Afifi, Astrida; Dwiyanti, Sri; Kusstianti, Nia; Wilujeng, Biyan Yesi (Jurnal Tata Rias, 2025)
Currently, many people use make-up as the main support for their profession, one of which is the product catalog model that makes make-up the main thing, so a perfect appearance is needed and gives a good impression to support the value of the product worn. This study aims to determine the difference in the results of the comparison of the proportion of liquid and cream foundations on the results of make-up on the product catalog model with oily skin types, using 2 samples of foundation proportions with different ratios of liquid and cream foundations. This type of research is a quantitative descriptive study with a quasi-experimental design of the one-shot case study type. The subjects of the study were 30 people, consisting of 3 make-up lecturers, 27 make-up experts or active students of make-up education at the State University of Surabaya. The data collection technique used an instrument sheet/questionnaire to assess the results of make-up with indicators of coverage, smoothness, evenness, durability, photo results and observer preferences. The results of the study obtained an average score of aspects that were averaged of 3.2 in sample X1 (proportion of foundation 2gr liquid: 2gr cream) and 3.57 in sample X2 (proportion of foundation 1gr liquid: 3gr cream). The calculation of statistical test results shows a Mann Whitney U value of 213.500 and a significance value (Asymp, Sig. 2-tailed) of less than 0.001 (p < 0.05). So there is a significant difference between sample data X1 and sample data X2 with sample data X2 having a higher score than sample data X1.